2013
DOI: 10.1523/jneurosci.2425-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

The Pro-Neurotrophin Receptor Sortilin Is a Major Neuronal Apolipoprotein E Receptor for Catabolism of Amyloid-β Peptide in the Brain

Abstract: Apolipoprotein (APO) E is the major risk factor for sporadic Alzheimer disease. Among other functions, APOE is proposed to sequester neurotoxic amyloid-β peptides (Aβ) in the brain, delivering them to cellular catabolism via neuronal APOE receptors. Still, the receptors involved in this process remain controversial. Here, we identified the pro-neurotrophin receptor sortilin as major endocytic pathway for clearance of APOE/Aβ complexes in neurons. Sortilin binds APOE with high affinity. Lack of receptor express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
114
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(122 citation statements)
references
References 62 publications
(95 reference statements)
7
114
0
1
Order By: Relevance
“…In detail, it was reported that BDNF could only induce Sorl1 expression in iPSC that carried at least one protective receptor haplotype [35]. The authors also reported that, in line with previous work [36], BDNF only reduced Aβ production in cells capable of inducing SORLA, highlighting the importance of the interplay between SORLA and BDNF in the disease situation. The relevance of the here described SORLA-dependent control of synapsins should be explored in the context of BDNFdependent synaptic modulation in AD in future studies.…”
Section: Discussionsupporting
confidence: 70%
“…In detail, it was reported that BDNF could only induce Sorl1 expression in iPSC that carried at least one protective receptor haplotype [35]. The authors also reported that, in line with previous work [36], BDNF only reduced Aβ production in cells capable of inducing SORLA, highlighting the importance of the interplay between SORLA and BDNF in the disease situation. The relevance of the here described SORLA-dependent control of synapsins should be explored in the context of BDNFdependent synaptic modulation in AD in future studies.…”
Section: Discussionsupporting
confidence: 70%
“…Sortilin is expressed in various cell types, especially in the nervous system, including in cortical and hippocampal neurons, glia, and sympathetic neurons (7), as well as in nonneuronal tissue, such as that in muscle, liver, lung, testis, and thyroid gland. In line with this broad tissue distribution, sortilin has been implicated in various disorders, including Alzheimer's disease (8), frontotemporal lobar dementia (9), and seizures (10), as examples of CNS diseases, as well as in dyslipidemia and in the risk for myocardial infarction (11,12).…”
mentioning
confidence: 98%
“…In this context, ApoE, a component of lipoproteins (primarily chylomicrons, VLDL, and a subset of HDL particles), facilitates entry into cells by acting as a ligand for the low-density lipoprotein receptor (LDL-R), LDL-R like protein (LRP), heparan sulfate proteoglycans, and additional non-canonical receptors (Mahley and Rall 2000;Carlo et al 2013). E4 is highly enriched in VLDL particles due to its altered lipid-binding region that shows a preference for binding triglyceride-enriched particles.…”
Section: Hyperlipidemiamentioning
confidence: 99%